2019
DOI: 10.1016/j.jshs.2019.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of breaking up sitting time in mainstream and special schools with a cognitively challenging motor task

Abstract: Highlights Breaking up sitting with a cognitively challenging motor task seemed to be feasible in mainstream primary schools. The cognitively challenging motor task was less feasible for use in special schools, but its feasibility would improve by tailoring the task to the specific abilities and needs of participants. In mainstream schools, the task seemed to be more appropriate for children between 6 and 8years of age. In special school… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
31
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 61 publications
5
31
1
Order By: Relevance
“…At the interpersonal level (i.e., student and peer factors), only one third of participants perceived observing disruptive student behaviour as a barrier to providing CBPA, whereas almost half the participants reported perceiving it as neither a facilitator nor barrier. This finding is in contrast to other studies conducted in Australia where behavioural challenges with students in Prep/kindergarten to Year 6 have been reported as a barrier for implementing short PA breaks into the school day (Mazzoli et al 2019;Watson et al 2019). Notably, one of the strongest facilitators for providing CBPA (in quantitative responses) identified by participants in this study was observing an improvement in student engagement during or following CBPA.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…At the interpersonal level (i.e., student and peer factors), only one third of participants perceived observing disruptive student behaviour as a barrier to providing CBPA, whereas almost half the participants reported perceiving it as neither a facilitator nor barrier. This finding is in contrast to other studies conducted in Australia where behavioural challenges with students in Prep/kindergarten to Year 6 have been reported as a barrier for implementing short PA breaks into the school day (Mazzoli et al 2019;Watson et al 2019). Notably, one of the strongest facilitators for providing CBPA (in quantitative responses) identified by participants in this study was observing an improvement in student engagement during or following CBPA.…”
Section: Discussioncontrasting
confidence: 99%
“…However, findings reported in that review were from studies conducted predominantly in the United States. Several studies conducted in Australia (Usher and Anderton 2014;Macdonald et al 2014;Mazzoli et al 2019;Watson et al 2019) have also reported insufficient time as a major barrier to implementing CBPA and this related to difficulties scheduling PA opportunities into the regular school class routine due to an already crowded curriculum. However, this is the first study to seek feedback from school staff regarding the factors influencing the provision of CBPA to children specifically in the early years of school in Australia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of fundamental motor skills (FMS) has been considered as the foundation of competently performing different types of physical activity (PA), as children need to first develop these essential movement skills to most effectively engage in PA behaviors [1]. In general, children's FMS are developed through various types of PA [2,3]. Indeed, previous research has indicated FMS development to be a key determinant in promoting PA participation, physical fitness, and other health-related outcomes as these motor skills are the basis for performing more complex PA in the future [4].…”
Section: Introductionmentioning
confidence: 99%
“…Pain-associated cognition has been extensively studied and is defined as the psychological processes associated with attention, memory, reasoning, and executive functions [4][5][6]. Cognition and pain are closely related, and cognitive dysfunction is regarded as a comorbidity of the experience of pain [2].…”
Section: Introductionmentioning
confidence: 99%